Effect of applied voltage and epoxy suspension’s ageing time on sheet resistance of electrodeposited epoxy coatings - Mohd Halim, Nurhaliana Shazwani; Nik Ab Rashid, Nik Ahmad Luqmanul Hakim; Lau, Kok Tee; Haji Azlan, Umar Al-Amani (Microscopy Society of Malaysia, 2025)
This study investigates the effect of applied voltages and epoxy suspension’s ageing time on the sheet resistance of electrodeposited epoxy coatings. Electrophoretic deposition (EPD) was employed as a coating technique due to its precise control over thickness and uniformity, making it suitable for electrical applications. Different applied voltages (i.e. 30, 40, and 60 V) and epoxy ageing times (1, 72, and 144 hours) were examined to understand their impact on the resulting coating's sheet resistance. Characterisations of the electrodeposited epoxy coatings were conductedusing the four-point probe method, weight gain measurement, field emission scanning electron microscopy and energy-dispersive X-ray spectroscopy. The results indicate that both the applied voltage and epoxy suspension’s ageing time significantly affect coating thickness and sheet resistance, with highest sheet resistance value of 818.0 9 kΩ/sq.is achieved at an applied voltage of 60 V and an hour ageing time. Higher voltages initially increase sheet resistance, but this effect diminishes with longer ageing times. These findings are essential for industries utilising epoxy coatings, suggesting that adopting the optimal applied voltage and epoxy suspension’s storing time can enhance coating performance and reliability. The study provides insight into tailoring electrodeposited epoxy coatings for customised sheet resistance properties, contributing to advancements in materials for electrical application.